A LabVIEW‐based TDLAS methane detection system using a wavelet denoising method. Issue 5 (3rd November 2021) - Ye, Weilin; Xu, Xiaohuan; Peng, Changxin; Xiao, Xupeng; Xia, Zikun; Liu, Weihao; Luo, Wenxuan; Wu, Fupei; Wu, Tao
Abstract: A methane detection system based on tunable diode laser absorption spectroscopy (TDLAS) using LabVIEW platform was demonstrated. To suppress the noise interference in the system, a wavelet denoising method was studied and experiments with different parameters were carried out. With the threshold of Hard, the wavelet basis of Coif5 and the rule of Heursure, high frequency noises of the sensor can be effectively decreased with the harmonic amplitude increased. Experiments showed that, the 1 σ minimum detection limit (MDL) was 23.68 ppbv (part per billion of volume) with an integration time of 300 s.